Knowledge and awareness on testicular cancer and practice of testicular self-examination among male undergraduate students of Kulliyyah of Allied Health Sciences, IIUM Kuantan - Hasmudin, Muhammad Hafiz Hilmi; Moey, Soo Foon; Che Mohamed, Norfariha (IJAHS, IIUM, 2021)
Introduction: Testicular cancer (TC) commonly occurs among young men aged 20 to 34 years old. However, many young men are not aware of the disease which could cause the disease to metastasize. Early detection of TC is crucial to decrease fatality due to late diagnosis of the disease. Testicular self-examination (TSE) is the easiest and cheapest method that can be performed by oneself whether one is suffering from TC. Currently, the awareness of TC and the practice of TSE is relatively low in Malaysia. Objective/aim: This cross-sectional study aimed to ascertain the level of knowledge, awareness and practice of TC and TSE among undergraduate students at the International Islamic University Malaysia (IIUM). Materials and methods: Eighty-seven male students from the Kulliyyah of Allied Health Sciences were randomly selected to participate in the study. A set of questionnaires was developed and the Cronbach’s alpha obtained was 0.7. A Google Form was used to obtain the data which was then analyzed using SPSS Version 26. Spearman rho correlation was utilized to determine the correlations between the level of knowledge of TC and level of awareness of TC as well as the practice of TSE. The statistical level of significance was set at p<0.05. Results: The study indicated that most of the respondents have moderate knowledge and awareness of TC. However, most did not perform TSE perceiving that they were not susceptible to TC. The study indicated that knowledge, awareness and practice of TSE are correlated (p-value <0.05), although the correlation was weak (r-value <0.5). Conclusion: TC screening should be made compulsory as a routine medical health check-up to aid in early detection of TC and decrease fatality due to late diagnosis.